Antenatal identification of early- and late-onset fetal growth restriction and the possible impact of the introduction of cerebroplacental ratio: Effect on perinatal and childhood outcome - Emma Hertting; Lotta Herling; Pelle G. Lindqvist; Eva Wiberg-Itzel (PLoS ONE, 2025)
Objective To investigate the effect of antenatal identification of small for gestational age (SGA) fetuses on perinatal and childhood outcomes, separately analyzing early- and late-onset fetal growth restriction (FGR). Materials and methods A register-based cohort study of all newborns born SGA, delivered in Stockholm in 2014 and 2017, n = 5499. Ultrasound reports of fetuses born SGA were reviewed and fetuses identified as SGA with ultrasound before birth were further defined as early- or late-onset FGR according to established criteria. Data from the medical chart for maternity and delivery was linked to nationwide Swedish registers. Adverse outcomes for antenatally non-identified SGA/FGR newborns and fetuses identified as early- or late-onset FGR were compared using logistic regression models. A composite outcome, severe adverse outcome, was constructed and defined as at least one of the following: stillbirth, severe newborn distress, severe neonatal outcome, severe childhood outcome. Individual components of the composite outcome were analyzed as secondary outcomes. Results Identified early-onset FGR fetuses had an increased risk for severe adverse outcome, compared to non-identified SGA/FGR (aOR 1.81, 95% CI 1.25–2.61), in contrast to late-onset FGR fetuses (aOR 1.14, 95% CI 0.78–1.67). Identified early-onset FGR had a decreased risk of stillbirth (aOR 0.47, 95% CI 0.23–0.96), an increased risk of severe newborn distress (aOR 2.80, 95% CI 1.79–4.39) and severe childhood outcome (aOR 3.00, 95% CI 1.51–5.94), compared to non-identified SGA/FGR. Identified late-onset FGR was only associated with an increased risk of severe childhood outcome (aOR 1.91, 95% CI 1.04–3.52). Conclusion Identified early-onset FGR fetuses benefited from identification with a decreased risk of stillbirth at the price of an increased risk for severe newborn and childhood outcomes. For late-onset FGR the advantages were undetectable; identification was associated with an increased risk for severe childhood outcome, while the negative association with stillbirth did not reach significance.